2000
DOI: 10.1038/emm.2000.13
|View full text |Cite
|
Sign up to set email alerts
|

The mucosal adjuvanticity of two nontoxic mutants of Escherichia coli heat-labile enterotoxin varies with immunization routes

Abstract: Escherichia coli heat-labile enterotoxin (LT), which causes a characteristic diarrhea in humans and animals, is a strong mucosal immunogen and has powerful mucosal adjuvant activity towards coadministered unrelated antigens. Here we report the different mucosal adjuvanticity of nontoxic LT derivatives, LTS63Y and LT∆110/112, generated by immunizing through two different mucosal routes. Intragastric (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…On the other hand, an association between the cytotoxicity of the protein and its ability to induce cytokine release has already been suggested [43]. …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, an association between the cytotoxicity of the protein and its ability to induce cytokine release has already been suggested [43]. …”
Section: Discussionmentioning
confidence: 99%
“…LT and CT are effective mucosal adjuvants; however, they cannot be used in humans due to their toxicities. In order to obtain nontoxic mucosal adjuvants with immunogenic activity, different mutants have been generated by site-directed mutagenesis [14,[38][39][40][41][42][43][44][45][46][47]. Our previous study demonstrated that LT R72DITH , which is a mutated form of LT R72 [14], is a new LT mutant with Glu→Asp, Val→Ile, Ile→Thr, and Tyr→His substitutions at positions 229, 230, 232, and 233, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In initial attempts, mutant holotoxins were engineered which targeted single-point amino acid substitutions at amino acids in the A polypeptides which were considered to be critical for ribosylation activity. While many of these mutant holotoxins [e.g., CT(E29H) [92] LT-I(H44A) [93], LT-I(A69G) [3], LT-I(S61F) [94,95], LT-I(S63K) [10], LT-I(S63Y) [96], and LT-I(A72R) [97], LT-I(E112K) [94,95]] (mutants will be noted by the single letter code for the amino acid in wt HLT, the position of the amino acid in the polypeptide, and the single letter code for the substituted amino acid) retained adjuvant activities, further evaluation demonstrated that mutant enterotoxins CT(E29H), LT-I(H44A), LT-I(A72R), and LT-I(A69G) retained residual enzymatic activity. Additional mutant enterotoxins were engineered to alter other properties of the enterotoxins required for full toxic activity including LT-I(R192G) [9], a mutant holotoxin in which a proteolyticallysensitive site within the A2 domain of the A polypeptide required for full toxicity was disrupted with a glycine for arginine substitution at amino acid position 192 of the A polypeptide.…”
Section: Detoxified Hltmentioning
confidence: 99%